Character Building Through the Waste Bank Management Program for Early Childhood - Kasmi, K; Katoningsih, Sri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research is to instill awareness in students at Muslimat 01 Jatipuro Kindergarten about environmental cleanliness, to provide lessons on waste management and to establish a waste bank that is expected to create a healthy and clean environment. In addition, the existence of this waste bank is intended to encourage students’ creative learning by utilizing waste. Methodology: This research is descriptive qualitative with a case study at TK Muslimat 01 Jatisobo, Jatipuro, Karanganyar. Data collection was carried out through interviews, observation, and documentation. The data were analyzed using a descriptive method to obtain a clearer and more detailed picture of the situation based on collected data, which were then classified and interpreted to analyze existing problems. Results: The results showed that the implementation of a character-building strategy through the waste bank management program successfully supported character cultivation for early childhood. Applications/Originality/Value: This research is that waste bank programs can be developed as an educational model for early childhood institutions to instill environmental awareness, promote healthy habits, and stimulate creativity by making students actively involved in managing waste sustainably.